Welcome to HorrorLand : a survival guide. (New York : Scholastic, 2009)
Offers survival tips and information for young readers on the evils that await in HorrorLand, and discusses the werewolves in Wolfsbane Forest, the disappearances of kids who enter the park, the mystery behind the lack of mirrors, and more.
4.8
5-8
Keywords: Amusement parks -- Juvenile fiction; Amusement parks -- Fiction; Horror stories; Amusement parks -- Fiction; Horror fiction; Horror fiction